1989
DOI: 10.1002/jhrc.1240120309
|View full text |Cite
|
Sign up to set email alerts
|

Inner wall coating of micro‐LC columns. Wall effects in LC

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…[76][77][78][79][80][81][82]), but also by column parameters (such as column blank material, frit selection, etc. [76,[83][84][85][86]). The majority of these suggested packing techniques are empirically developed and mainly based on assumptions and trial and error methods.…”
Section: Column Developmentsmentioning
confidence: 99%
“…[76][77][78][79][80][81][82]), but also by column parameters (such as column blank material, frit selection, etc. [76,[83][84][85][86]). The majority of these suggested packing techniques are empirically developed and mainly based on assumptions and trial and error methods.…”
Section: Column Developmentsmentioning
confidence: 99%
“…The values are somewhat scattered due to the different packing conditions and column design, but seem to be located at the low end of the typical range (500-1000). Loose packing of packed capillary columns is likely to occur as a result of the wall effect, as discussed by Verzele et al (19). It is interesting to note that the loosely packed column was more efficient than the densely packed one, although the author did not refer to this (20).…”
Section: Column Performancementioning
confidence: 94%
“…Therefore, backflushing should be avoided for packed capillary columns. Verzele et al have reported that the use of wall-coated fused silica capillaries can produce more stable beds and higher efficiencies for 5-pm particles (19). Yang obtained better efficiencies with 2-pm particles using wall-coated capillaries (21).…”
Section: Column Performancementioning
confidence: 98%
“…Karlsson and Novotny reported the evaluation of slurry packed capillary columns with inner diameters in the range of 44 -265 lm, using constant flow for packing [39]. Verzele and co-workers studied the walleffect in micro-LC columns (250 and 320 lm ID) and showed that an elastic inner wall coating in the fused silica capillary stabilizes the packed bed, increasing column efficiency and life expectancy [42]. Kennedy and Jorgenson [40] prepared and evaluated slurry packed capillary columns with small inner diameters (20 -50 lm) packed with 5 lm porous octylsilane-modified silica particles.…”
Section: Slurry Packing Of Capillary Columnsmentioning
confidence: 98%